The Polysemy and Hyponymy of Mandarin Spatial Prepositions and Localisers: Building Semantic Maps from the Ground up - Ursini, Francesco-Alessio; Rao, Qi; Zhang, Yue Sara (Frontiers in Communication, 2021)
The goal of this paper is to offer an overview of polysemy patterns in Mandarin’s chief spatial categories: prepositions (e.g. zai) and simple and compound localisers (respectively qian, qian-mian). The paper presents data from an elicitation study that shows how speakers can access multiple senses and sense relations for the vocabulary items belonging to these categories. The paper shows that while prepositions can potentially cover any spatial relation in the opportune context (e.g. zai ‘at’), localisers select increasingly specific senses (e.g. qian ‘front’, qian-mian ‘front side’). The paper also shows how speakers can access hyponym-like sense relations emerging from these patterns (e.g. qian-bian covering a more specific sense than qian). Crucially, semantic factors such as ‘distance’ and ‘reference’ determine the strength of these sense relations. The paper offers an account of these data based on the “semantics maps” model, which captures senses and senses’ relations via the clusters of places, regions and directions they denote. It is proposed that the model is consistent with previous works on the polysemy of spatial senses, and sheds light on how Mandarin offers a distinctive organisation of this domain.